(untitled) (Clinics, 2013)
OBJECTIVE: To evaluate the effects of the levels of glycemic control on the frequency of clinical complications following invasive dental treatments in type 2 diabetic patients and suggest appropriate levels of fasting blood glucose and glycated hemoglobin considered to be safe to avoid these complications. METHOD: Type 2 diabetic patients and non-diabetic patients were selected and divided into three groups. Group I consisted of 13 type 2 diabetic patients with adequate glycemic control (fasting blood glucose levels